Is cause-related marketing a winning strategy? An event study analysis. Issue 1 (2nd January 2020) - Das, Neel; McNeil, Chris; Pouder, Richard W.; Daly, Joseph P.
ABSTRACT: Cause-related marketing (C-RM) is the fastest-growing category of U.S. sponsorship spending. However, extant research provides no examination of whether investments in C-RM are economically worthwhile. This event study of 127 cause-related announcements from 1991 through 2011 shows a mean cumulative abnormal return of .74% occurring after two trading days. This indicates that C-RM programs are a good investment on average. Cross-sectional analysis of returns reveals that abnormal returns are augmented when the cause is tied to a special product and when firms pledge an additional concurrent donation. But the returns are depressed when a firm has high free cash flow.